2017
DOI: 10.15517/rgac.v0i56.29238
|View full text |Cite
|
Sign up to set email alerts
|

Geología del cuadrante Tapantí (1:50 000), Costa Rica

Abstract: ABSTRACT:We present a geologic map of the Tapantí quadrangle, which is located in the central region of Costa Rica and belongs to the Central Costa Rica Deformed Belt (CCRDB). The CCRDB is a consequence of the interaction of the Cocos Ridge and the Western edge of the Panama microplate. The oldest rocks mapped in this work are Miocene in age and theyvbelongs to Pacacua, Peña Negra and Coris formations, than form the western edge of the Candelaria basin. Three igneous events were distinguished. First, the Mioce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 13 publications
1
2
0
12
Order By: Relevance
“…This site model uses shear wave velocities in the top 30 ms (VS30), and it contains velocities in the Central Valley ranging from 320 to 470 m/s. The authors observed that such values are in agreement with the sedimentary soil deposits that characterize the geology of the region (Sojo et al, 2017). The same site model was used for the loss assessment in this study.…”
Section: Vulnerability and Definition Of The Earthquake Scenario For The Gma Of San Josésupporting
confidence: 79%
“…This site model uses shear wave velocities in the top 30 ms (VS30), and it contains velocities in the Central Valley ranging from 320 to 470 m/s. The authors observed that such values are in agreement with the sedimentary soil deposits that characterize the geology of the region (Sojo et al, 2017). The same site model was used for the loss assessment in this study.…”
Section: Vulnerability and Definition Of The Earthquake Scenario For The Gma Of San Josésupporting
confidence: 79%
“…6.a), siendo caracterizados por cenizas color café/rojiza de texturas medias a gruesa, con espesores métricos no superior a 20 m aprox; las cuales poseen una continuidad geográfica lateral en otros puntos geográficos en la localidad de Paraíso (Dondoli & Torres, 1954, Krushensky;1972). No obstante, para Sojo et al, (2017) y Sojo (2018) son interpretadas como posibles frentes de meteorización de las lavas subyacentes (Figura.6.b) propias de la formación Reventado (Miembro Paraíso), denominándolas como: Capa de Laterita El Rincón, siendo un término que engloba la ubicación de la localidad tipo y el material (Sojo, 2018). Figura 6.…”
Section: Principales Características Geológicas Asociadas Con El áRea De Interésunclassified
“…La Formación Reventado guarda un carácter regional y representativo directamente en el sitio de interés (Sojo, 2018); por lo que no fue posible observar considerables espesores de otros materiales de índole volcánico que fueran, geológicamente, más recientes a las fechas definidas por Sojo et al, (2017) en el orden 0.6 Ma, para las lavas fracturadas del Miembro Paraíso, siendo estas preponderantes en la formación del supuesto cerro/ volcán Santa Lucía. Todo lo anterior permite descartar una local y reciente expulsión así como consecuente acumulación de materiales volcánicos poco consolidados, derivados un foco eruptivo dentro del área de estudio, además de pocas evidencias de diferentes grados de hidrotermalismo en los materiales existentes por una fuente de calor "in situ".…”
Section: Discusión Materiales Geológicos Asociados Con La Formación Del Aparente Cerro/volcán Santa Lucíaunclassified
See 2 more Smart Citations